2017
DOI: 10.1108/md-12-2015-0566
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organizational factors on board roles

Abstract: Purpose Using a contingency approach, the purpose of this paper is to study how organizational factors (such as the organizational life cycle, firm size, firm ownership concentration and firm technology) determine the relative importance of the monitoring and provision of resources roles provided by board members. Design/methodology/approach This paper highlights the importance of contingency factors in carrying out board’s roles using a sample of 579 European firms registered in the STOXX Europe 600 index. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 138 publications
(171 reference statements)
2
18
0
Order By: Relevance
“…Nevertheless, it is rarely used to its full extent in differentiating between BVC (idea creation and implementation) and BVP (idea ratification and monitoring) for the apparent lack of available proxies in secondary IPO data. A notable exception is the recent investigation by Sánchez, Guerrero‐Villegas and Hurtado González (), who employ a factor‐analytic approximation of BVP based on such secondary data. This shows the possibilities of enriching this research field beyond our approach of utilizing a specific governance context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is rarely used to its full extent in differentiating between BVC (idea creation and implementation) and BVP (idea ratification and monitoring) for the apparent lack of available proxies in secondary IPO data. A notable exception is the recent investigation by Sánchez, Guerrero‐Villegas and Hurtado González (), who employ a factor‐analytic approximation of BVP based on such secondary data. This shows the possibilities of enriching this research field beyond our approach of utilizing a specific governance context.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we take advantage of the German two‐tier board, which allows us to isolate the BVP as a function and thereby overcome methodological issues of prior studies. Although the logic of the two‐tier board is not immediately generalizable to other contexts, a shift in how BVP vs BVC is measured and observed (see also Sánchez, Guerrero‐Villegas and Hurtado González, ) can advance our understanding of how boards contribute to performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to diversity, board capital theory argues that board diversity implies a bundle of knowledge, skills, experiences and information that reflect the breadth of the resources that directors bring to the board [33]. These resources represent the human capital of the board, referring to the knowledge and expertise of directors at an individual level; and also include the social capital that emerges from the board members' networks and relationships [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…We found several cases in our analysis where citing authors miscited an MA to justify exploring a relationship that the original MA never addressed (e.g., Alabede, 2016; Potosky, 2016). Several papers cited Dalton et al’s (1998) MA as providing evidence for a significant and meaningful relationship between board of director composition or board leadership structure and firm financial performance despite the fact that Dalton et al found exactly the opposite (i.e., no relationship) (e.g., Matthew, Ibrahim, & Archbold, 2016; Sanchez, Guerrero-Villegas, & Gonzalez, 2017). This has resulted in a thriving stream of research on this relationship that often results in the citing authors “surprisingly” finding no relationship between these variables in their own data.…”
Section: Findings and Discussionmentioning
confidence: 99%